1997
DOI: 10.2166/wst.1997.0362
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal from wastewater with high ammonia nitrogen concentration via shorter nitrification and denitrification

Abstract: Shorter nitrification is reached through Nitrobacter bacteria activity inhibition. Nitrobacter bacteria responsible for nitrite nitrogen oxidation are sensitive to free ammonium. The presence of free ammonium depended on a high ammonia nitrogen concentration in wastewater and its pH. It was the pH of the wastewater that was the decisive parameter in Nitrobacter bacteria activity inhibition in stable temperatures and at stable ammonia nitrogen concentrations. Reaction control in the aeration phase of the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 0 publications
1
29
0
7
Order By: Relevance
“…In conventional wastewater treatment process, ammonia concentration generally would be controlled at the lower level to satisfy discharge standard. However, fast-growth-pattern AOB will accumulate in partial nitrification reactors because of high ammonia concentration (Surmacz-Gorska et al 1997). These also demonstrate why it is easy to achieve partial nitrification to treat wastewater with high concentrations of ammonia, but difficult to implement and maintain steady partial nitrification with treatment of common domestic wastewater (Sliegrist et al 1998;van Dongen et al 2001).…”
Section: Control Of Substrate Concentration and Loadmentioning
confidence: 99%
“…In conventional wastewater treatment process, ammonia concentration generally would be controlled at the lower level to satisfy discharge standard. However, fast-growth-pattern AOB will accumulate in partial nitrification reactors because of high ammonia concentration (Surmacz-Gorska et al 1997). These also demonstrate why it is easy to achieve partial nitrification to treat wastewater with high concentrations of ammonia, but difficult to implement and maintain steady partial nitrification with treatment of common domestic wastewater (Sliegrist et al 1998;van Dongen et al 2001).…”
Section: Control Of Substrate Concentration and Loadmentioning
confidence: 99%
“…Abiotic factors like temperature, pH and nutrients have a strong influence on the growth and activity of micro-organisms. -Gorska et al (1997) found in their experiments that the pH of the wastewater was the decisive parameter in NOB activity inhibition. Tonkovic (1998) on the other hand came to the conclusion from sewage plant monitoring data with lab scale reactor tests that nitrite accumulation is independent of the pH, but is rather due to low dissolved oxygen, suppressing Nitrobacter.…”
Section: Abiotic Factors Influencing Nitrite Accumulationmentioning
confidence: 99%
“…The biomass growth rate can be in range of 0.3 -0.75 gSDM/gsub rem [37]. Similarly high nitrogen removal efficiency in SND process in continuous reactor (about 90%) can be achieved at certain pH and N-NH4 concentration [38]. The nitrite concentration rise indicates that the nitrification process has stopped after the first phase.…”
Section: Figure 3 Elementary Processes Of Nitrification and Denitrifmentioning
confidence: 99%